2016
DOI: 10.1590/bjpt-rbf.2014.0151
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of Kinesiotaping does not enhance functional performance and joint proprioception in healthy young males: Randomized controlled trial

Abstract: ObjectivesThe aim of this study was to investigate the effects of continuous (48-hour) use of Kinesiotaping (KT) on functional and proprioceptive performance in healthy, physically active men.MethodTwenty-six healthy, physically active men (21.8±2.2 years old) were randomly allocated into two groups: 1) Kinesiotaping group (KG, tape applied with 40% tension for rectus femoris activation); 2) Control (CG, tape applied over rectus femoris without additional tension). Subjects attended the laboratory on five sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
2
18
0
1
Order By: Relevance
“…Our results indicate that there were no significant interactions in pain, SH distance, VJH, and VJP between the groups and time points (after the MFP, post-KT, and 24-post KT). This finding is consistent with that of previous studies that reported that KT application did not immediately enhance functional performance in healthy individuals, regardless of subject deception and changes in tape tension [14,21,22]. On the other hand, Mendez-Rebolledo et al found that KT increased VJH and ground reaction force only 72 h, but not 24 h, after KT application on the gluteus maximus, biceps femoris, longissimus, rectus femoris, and gastrocnemius muscles in male athletes [22].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results indicate that there were no significant interactions in pain, SH distance, VJH, and VJP between the groups and time points (after the MFP, post-KT, and 24-post KT). This finding is consistent with that of previous studies that reported that KT application did not immediately enhance functional performance in healthy individuals, regardless of subject deception and changes in tape tension [14,21,22]. On the other hand, Mendez-Rebolledo et al found that KT increased VJH and ground reaction force only 72 h, but not 24 h, after KT application on the gluteus maximus, biceps femoris, longissimus, rectus femoris, and gastrocnemius muscles in male athletes [22].…”
Section: Discussionsupporting
confidence: 92%
“…Tape tension is a key factor of the KT method [14]. One study showed that tape tension can improve proprioceptive feedback and facilitate correct posture and movement, even after removal of the tape [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations